Building Sustainable Partnerships to Strengthen Pediatric Capacity at a Government Hospital in Malawi - Eckerle, Michelle; Crouse, Heather L.; Chiume, Msandeni; Phiri, Ajib; Kazembe, Peter N.; Friesen, Hanny; Mvalo, Tisungane; Rus, Marideth C.; Fitzgerald, Elizabeth F.; McKenney, Allyson; Hoffman, Irving F.; Coe, Megan; et al. (Frontiers in Public Health, 2017)
Introduction To achieve sustained reductions in child mortality in low- and middle-income countries, increased local capacity is necessary. One approach to capacity-building is support offered via partnerships with institutions in high-income countries. However, lack of cooperation between institutions can create barriers to successful implementation of programs and may inadvertently weaken the health system they are striving to improve. A coordinated approach is necessary. Background Three U.S.-based institutions have separately supported various aspects of pediatric care at Kamuzu Central Hospital (KCH), the main government referral hospital in the central region of Malawi, for several years. Within each institution’s experience, common themes were recognized which required attention in order to sustain improvements in care. Each recognized that support of clinical care is a necessary cornerstone before initiating educational or training efforts. In particular, the support of emergency and acute care is paramount in order to decrease in-hospital mortality. Through the combined efforts of Malawian partners and the U.S.-based institutions, the pediatric mortality rate has decreased from >10% to <4% since 2011, yet critical gaps remain. To achieve further improvements, representatives with expertise in pediatric emergency medicine (PEM) from each U.S.-based institution hypothesized that coordinated efforts would be most effective, decrease duplication, improve communication, and ensure that investments in education and training are aligned with local priorities. Call to Action Together with local stakeholders, the three U.S.-based partners created a multi-institutional partnership, PACHIMAKE (Pediatric Alliance for Child Health Improvement in Malawi at Kamuzu Central Hospital and Environs). Representatives from each institution gathered in Malawi late 2016 and sought input and support from local partners at all levels to prioritize interventions which could be collectively undertaken by this consortium. Long- and short-term goals were identified and approved by local partners and will be implemented through a phased approach. Conclusions The development of a novel partnership between relevant stakeholders in Malawi and U.S.-based partners with expertise in PEM should help to further decrease pediatric mortality through the coordinated provision of acute care expertise and training as well as investment in the development of educational, research, and clinical efforts in pediatric emergency medicine at KCH.